Green and sustainable cellulose-derived humidity sensors: A review. (15th October 2021) - Li, Zixiu; Wang, Jian; Xu, Yongjian; Shen, Mengxia; Duan, Chao; Dai, Lei; Ni, Yonghao
Abstract: Cellulose, as the most abundant natural polysaccharide, is an excellent material for developing green humidity sensors, especially due to its humidity responsiveness as a result of its rich hydrophilic groups. In combination with other components including carbon materials and polymers, cellulose and its derivatives can be used to design high-performance humidity sensors that meet various application requirements. This review summarizes the recent advances in the field of various cellulose-derived humidity sensors, with particular attention paid to different sensing mechanisms including resistance, capacitance, colorimetry and gravity, and so on. Furthermore, the roles of cellulose and its derivatives are highlighted. This work may promote the development of cellulose-derived humidity sensors, as well as other cellulose-based intelligent materials. Graphical abstract: Unlabelled Image Highlights: Green and sustainable cellulose-derived humidity sensors. Cellulose and its derivatives acting as substrates and/or sensing materials in humidity sensors. Different sensing mechanisms in cellulose-derived humidity sensors discussed.